2022
DOI: 10.1002/cpt.2743
|View full text |Cite
|
Sign up to set email alerts
|

Population PK and Semimechanistic PK/PD Modeling and Simulation of Relugolix Effects on Testosterone Suppression in Men with Prostate Cancer

Abstract: Relugolix, the first orally active, nonpeptide gonadotropin-releasing hormone receptor antagonist, is approved in the United States and the European Union for the treatment of adult patients with advanced prostate cancer. The recommended dosing regimen is a 360-mg loading dose followed by a 120-mg daily dose. Relugolix and testosterone concentration data and clinical information from two phase I studies, two phase II studies, and the phase III safety and efficacy study (HERO) were used to develop a population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Simulation studies showed that treatment interruptions of up to 7 days did not significantly impact testosterone suppression with relugolix (Table 2). 34 Interestingly, following a 7-day treatment interruption, simulated testosterone concentrations predicted that the percentage of patients on relugolix who remained at castration levels was still higher (97.3%) than the observed population treated with leuprolide (88.8%) during the HERO study (Table 1). After a temporary interruption of 7 days or longer, a loading dose of 360 mg of relugolix is recommended.…”
Section: Adherence To Oral Antiandrogens Vs Injectable Adt In Pcmentioning
confidence: 94%
See 3 more Smart Citations
“…Simulation studies showed that treatment interruptions of up to 7 days did not significantly impact testosterone suppression with relugolix (Table 2). 34 Interestingly, following a 7-day treatment interruption, simulated testosterone concentrations predicted that the percentage of patients on relugolix who remained at castration levels was still higher (97.3%) than the observed population treated with leuprolide (88.8%) during the HERO study (Table 1). After a temporary interruption of 7 days or longer, a loading dose of 360 mg of relugolix is recommended.…”
Section: Adherence To Oral Antiandrogens Vs Injectable Adt In Pcmentioning
confidence: 94%
“…35 The simulated testosterone concentrations are predicted to return to steady state approximately 13 days after the resumption of the 120-mg daily dose. 34…”
Section: Adherence To Oral Adt In Pc In Clinical Trial Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with prostate cancer had to have a castration level of testosterone (1.73 nmol/L or less). 22 Adequate hematologic, hepatic, and renal function were required for participation. Patients using concomitant CYP3Amodulating drugs, herbs, or food 14 days before the start of the study or within 5 half-lives of the drug and patients who smoked during or within 7 days before the start of the study were excluded.…”
Section: Study Design and Patientsmentioning
confidence: 99%